Correlations of psychological distress with plasma cytokine levels and gene mutations in acral and non-acral melanoma - Kim, Hong Euy; Shim, Hyun Jung; Jung, Chaeyong; Shin, Il Seon; Kim, Jae-Min; Yun, Sook Jung (Frontiers in Psychiatry, 2022)
Background: The presence of psychological distress has negatively affected the course and prognosis of melanoma. Psychological distress is influenced by cytokines and gene mutations, particularly in cancer, but no studies have investigated this phenomenon in melanoma patients. This study investigated the correlations of psychological distress, plasma cytokine levels, and gene mutations in melanoma patients, focusing on melanoma sites and TNM stages. Methods: This study prospectively evaluated melanoma patients who visited Chonnam National University Hwasun Hospital from September 2020 to March 2021. Melanoma sites were divided into acral and non-acral sites. Anxiety and depression were evaluated using the Hospital Anxiety and Depression Scale, and quality of life was evaluated with EuroQol-5 Dimensions. Plasma cytokine levels, and depression- and cytokine-related gene mutations were analyzed. Results: This study included 151 melanoma patients. Anxiety was found in 14.6% of the patients, and depression in 29.8%. The melanoma sites were not significantly associated with anxiety, depression, or quality of life. However, psychological distress was significantly associated with the plasma cytokines IL-2, IL-4, IL-5, IL-10, IL-12, TNF-α and IFN-γ. COMT, SLC6A4, SLC6A3, and IL-12b gene mutations were also associated with melanoma sites and TNM stage, anxiety, and QOL. Conclusion: Psychological distress was associated with plasma cytokine levels and depression- and cytokine-related gene mutations. Using psychiatric intervention and emotional support, cytokine levels related to melanoma can be changed, which may have positive effects on the prognosis and treatment of melanoma. More careful follow-up, evaluation, and management are needed for patients with gene mutations.